Pembangunan Aplikasi Penyedia Informasi Lowongan Pekerjaan Menggunakan Youtube API Pada Smartphone Android - Ervin Winardo Toepak; Issa Arwani; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Unemployment is a problem that still exists in Indonesia. The problem of unemployment occurs due to lack of job field compared to job applicants. The government itself has helped job applicants by providing job vacancy information obtained from the company. With the increasingly widespread of job vacancy information, then the applicants for job vacancies will be more and more. The more applicants who apply, then the selection process will also take a long time. In order for the selection process to be faster, then needed a solution that allows the selection process becomes more effective. In this research, an application that provide information about job vacancy will be built and will be equipped with video resume feature as a medium to promote job applicants to the company by implementing Youtube API. With the video resume, the company can save time to make the process of selecting labor. The results of this application usability level testing as a whole reached a value of 79.5 which indicates that this application has a good predicate in terms of usability